Authority of the Information Commission as a Quasi Judicial Institution in Resolving Public Information Disputes - Faradina, Ginar Listya (Indonesia Media Law Review, 2023)
The right to information is a guaranteed right in laws and regulations for every citizen. The promulgation of the Public Information Disclosure Act is a new era to ensure the fulfillment of the right to information. Within the framework of carrying out public information disclosure, of course we are faced with various public information disputes, namely disputes that arise between users of public information and public bodies. Along with the increasing demands and needs of the public in the constitutional legal system, various judicial institutions have been specifically formed and specifically mandated by the state legislation through to examine and decide disputes other than those that are the domain of the existing judiciary or are referred to as quasi-judicial or quasi-judicial institutions, one of which is the Information Commission. This writing examines the authority of the Information Commission as a quasi-judicial institution in resolving public information disputes through a non-litigation process. Which emphasized that one of the mandates of the UU KIP is the establishment of an Information Commission which has the authority to resolve public information disputes in a non-litigation manner, namely in the form of mediation and non-litigation adjudication. The information commission has special powers that are absolute, absolute, and cannot be transferred or given to other institutional bodies. The two main tasks of the position of the information commission are finalizing and establishing general policies related to public information services for public bodies.